2015
DOI: 10.1007/s12272-015-0662-z
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin attenuates learning and memory deficits in APP/PS1 mice through activation of Akt/Nrf2 signaling and inhibition of RAGE/NF-κB signaling

Abstract: Numerous studies have demonstrated that oxidative stress and inflammation play a pivotal role in the pathophysiology of Alzheimer disease (AD). Hesperidin (HP) has various pharmacological effects including anti-oxidative, anti-inflammatory and neuroprotective properties. In this study, APP/PS1 mice were used to evaluate the neuroprotective effects of HP. We reported that intragastric administration of HP (40 mg/kg) for 90 days significantly attenuated cognitive impairment in APP/PS1 mice. HP treatment suppress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…It is known that Nrf2 is compromised by age [109,110] and downregulated in AD [111], deficits replicated in different animal models [112,113]. Notably, our data indicate that Aβ challenge did not translate in a concomitant activation of Nrf2 and its downstream antioxidant response elements in spite of eliciting a severe ROS production in neuronal cells, findings consistent with the Nrf2 downregulation coexisting with the amply documented oxidative stress reported in AD [111,114].…”
Section: Discussionsupporting
confidence: 77%
“…It is known that Nrf2 is compromised by age [109,110] and downregulated in AD [111], deficits replicated in different animal models [112,113]. Notably, our data indicate that Aβ challenge did not translate in a concomitant activation of Nrf2 and its downstream antioxidant response elements in spite of eliciting a severe ROS production in neuronal cells, findings consistent with the Nrf2 downregulation coexisting with the amply documented oxidative stress reported in AD [111,114].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, several HMGB1 inhibition approaches, including TTP488, sRAGE-mesenchymal stem cells (MSCs), FPS-ZM1, matrine, pentamidine, hesperidin, and linguizhugan, have revealed promising outcomes in experimental AD models mainly by inhibiting RAGE expression, decreasing production of Aβ, reducing Aβ deposition, oxidative stress, and inflammatory cytokines, while improving spatial learning and memory (Table 2) [113][114][115][116][117][118].…”
Section: Effects Of Rage Inhibition In Admentioning
confidence: 99%
“…Suppressing NF-κB activity attenuates pain and inflammation in rats with osteoarthritis (25). Hesperidin has been reported to suppress oxidative stress and inflammation via activation of the protein kinase B/nuclear factor erythroid 2-related factor 2 signaling pathway, inhibition of the receptor for advanced glycation end products/NF-κB signaling pathway and further confers neuroprotection (26). In the current study, it was revealed that hesperidin significantly inhibited NF-κB activity in IL-1β-stimulated human OA chondrocytes.…”
Section: Discussionmentioning
confidence: 99%